The contribution of physical education and its effects on the development of fundamental motor skills in early childhood education (Research, Society and Development, 2022)
The manifestations of motor development stand out as a direct application of the work of specialized professionals in accordance with relevant contents. There are studies that have shown concern with child development and the direct cultural influence on motor performance. The objective of this study is to understand the contributions of Physical Education and its influence on the development of fundamental motor abilities in early childhood education. This is a literature review, conducted through a systematic and exploratory research, using the databases Lilacs, PubMed, Scielo and scientific articles available on the Google academic platform, in Portuguese and English, with date restrictions, between the years 2011 and 2022. Thus, we seek to offer information that can contribute to the managers of the teaching area, professionals in physical education degrees, and pertinent areas for the appropriate application in early childhood education, in order to inhibit probabilities of out-of-standard alterations in the motor profile, or to make them capable of identification when necessary.